Promoting early childhood oral health and preventing early childhood caries on Instagram - Lee, Victor H. K.; Kyoon-Achan, Grace; Levesque, Josh; Ghotra, Suhird; Hu, Ralph; Schroth, Robert J. (Frontiers in Oral Health, 2023)
Introduction Early childhood caries (ECC) is prevalent worldwide. Oral health promotion effectively utilizes key messages to educate parents/caregivers and the public on how to prevent ECC. Instagram is one of the biggest social media platforms, and could be used to promote early childhood oral health. The purpose of this study was to determine if and how young children's oral health is promoted and supported on Instagram. Methods This study used inductive content analysis to categorize, quantify, and interpret pictorial and textual data derived from Instagram posts containing the most commonly used ECC-related hashtags in their captions (determined by an extensive search through Instagram's search bar). Results A total of 1,071 images and 3,228 comments were analyzed based on 13 hashtags. The most common types of images were those of people (57.5%) and graphics/memes (37.8%). Most people were older children (32.5%) or adults (20.3%), and were White (19.6%) or Asian (18.5%). A majority of images had people posing (79.1%) in dental clinics (81.3%). Most graphics/memes were instructional/informational (76.3%). A total of 173 posts had substantial discussions that were positive/constructive in nature. The majority of discussions had at least one comment providing advice, tips, or explanations (79.8%), or had users requesting further information (73.4%). Conclusion As more people engage with social media, health professionals should consider the potential for Instagram as a tool to promote early childhood oral health and to prevent ECC. Our study shows that many different users are providing and consuming content related to ECC. Targeted messaging, monitoring of content, and professional guidance could be beneficial to those seeking oral health information on this platform.